Manajemen Kurikulum Merdeka Belajar dalam Menyukseskan Projek Penguatan Profil Pelajar Pancasila di SDN 04 Muara Pinang - Pebri Yanti; Khairiah Khairiah; Mindani Mindani (UIN Fatmawati Sukarno Bengkulu, 2024)
Independent learning curiculum management at public elemtary school 04 Muara Pinang is a crucial element in every educational form and model. Without effective curriculum management, education administrations will struggle to achieve educational objective and shape students who embody the Pancasila student profile. The aim of this research is to describe the management of independent leraning curiculum in the succes Project To Strengthen The Profile Of Pancasila Students. This qualitative descriptive research employed data collection techniques such as interviews, observations, and documentation. The findings indicate that the management of the independent learning curriculum is satisfactory. This is evident from the planning, which involves KKG in formulating the Annual Teaching Program (ATP), organizing by forming a teacher committee, curriculum development team, and facilitator team, implementing through the application of PMM and the realization of the learning process, as well as evaluating through assessment and supervision. The Project to Strengthen the Profile of Pancasila Students is well-executed. This is demonstrated by the planning phase, which involves the formation of a facilitator team, the implementation phase divided into three stages: the introduction phase via inspirational videos, real action taken in accordance with the theme, and follow-up evaluation to expand the impact and benefits of the project. Supporting factors for the implementation of the independent learning curriculum in the Project to Strengthen the Profile of Pancasila Students include the categorization as a driving school and adequate facilities and infrastructure. Conversely, inhibiting factors include the difficulty teachers face in handling students' diverse characters, challenges in adapting to digital tools, and limited subject-specific textbooks. So it can concluded that independent learning curiculum management in the succes Project To Strengthen The Profile Of Pancasila Students.